2014
DOI: 10.4162/nrp.2014.8.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Association between high sensitivity C-reactive protein and dietary intake in Vietnamese young women

Abstract: BACKGROUND/OBJECTIVESHigh sensitivity C-reactive protein (hsCRP) is a strong independent predictor of future cardiovascular disease (CVD) risk. We evaluated the relationship between hsCRP and dietary intake in apparently healthy young women living in southern Vietnam.SUBJECTS/METHODSSerum hsCRP was measured and dietary intake data were obtained using the 1-day 24-hour recall method in women (n = 956; mean age, 25.0 ± 5.7 years) who participated in the International Collaboration Study for the Construction of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…This is consistent with the observation that folate intake was protective against elevation of CRP above 28.5 nmol/L in lactating women from Kenya [60] and that young Vietnamese women with higher folic acid intake had lower CRP [61]. The absence of a relationship between folic acid deficiency and CRP during pregnancy is most likely because women in our study were receiving folic acid supplementation during pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the observation that folate intake was protective against elevation of CRP above 28.5 nmol/L in lactating women from Kenya [60] and that young Vietnamese women with higher folic acid intake had lower CRP [61]. The absence of a relationship between folic acid deficiency and CRP during pregnancy is most likely because women in our study were receiving folic acid supplementation during pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“… 36 The association between the effects of environmental changes (i.e. diet habit) experienced by immigrants or emigrants and CVD 37 or metabolic syndrome 38 has also been shown.…”
Section: What Has It Found? Key Findings and Publicationsmentioning
confidence: 99%
“…Earlier reports found a direct association between CRP concentrations and the risk of CVDs in different populations around the world. In a population-based study, two-fold higher mortality from CVDs was reported in serum CRP of > 3 mg/L, while the optimal level confirmed by the AHA and the CDC is < 1 mg/L 67 . In the Women's Health Study, by increasing quintiles of CRP (≤ 0.49, > 0.49 to 1.08, > 1.08 to 2.09, > 2.09 to 4.19, and > 4.19 mg/L), the corresponding relative risks of a first cardiovascular event were 1.0, 1.4, 1.6, 2.0, and 2.3 (P for trend < 0.001), in the adjusted model 68 .…”
Section: Discussionmentioning
confidence: 94%